Effect of Fe2O3 Nanoparticles Dust on the D.C Plasma Characteristics with Mirror Magnetron - Abdulghani, Shahad Emaduldeen; Abbas, Qusay A. (Iraqi Journal of Science, 2023)
In this paper, the effect of iron oxide nanoparticles dust (Fe2O3 NPs) on the parameters of DC electric discharge plasma under vacuum in argon gas was studied with the presence of a mirror magnetron behind the electrodes (cathode and anode) at constant pressure and with different amounts of Fe2O3 nanoparticles. Calculations presented a reduction of the plasma emission intensity with the NPs content. Both the plasma density (calculated by Stark’s broadening method) and the mean electron temperature (calculated using Boltzmann’s equation) decreased with increasing the Fe2O3 nanoparticles dust content, which indicates clearly the effect of dust density on restricting the movement of charge carriers, which in turn reduces inelastic plasma collisions.